The combination of pharmacogenetic and pharmacokinetic analyses to optimize clomipramine dosing in major depression: a case report. (31st October 2016) - Antoniazzi, Stefania; Tatulli, Alessandro; Falvella, Felicia S.; Cigliobianco, Michela; Paoli, Riccardo A.; Cattaneo, Dario; Cheli, Stefania; Bernardi, Francesca F.; Clementi, Emilio; Altamura, Carlo A.
Summary: What is known and objective: Polymorphisms in cytochrome P450 2D6 and 2C19 can lead to interindividual differences in drug plasma concentrations, affecting clomipramine efficacy. Pharmacokinetic and pharmacogenetic analyses may improve drug therapy. Case summary: We report the case of a depressed woman requiring higher doses than standard of clomipramine. Identification of low plasma drug levels led to extensive pharmacogenetic analyses of all genes and major functional polymorphisms reported to affect clomipramine metabolism. What is new and conclusion: Therapeutic drug monitoring and pharmacogenetic analyses may be useful in the investigation and optimization of clomipramine in standard‐dose non‐responders.